Prognostic Significance of Serum Proangiogenic Molecules in Patients with De Novo Non-Hodgkin Lymphomas - Pairaya Rujirojindakul; Arnuparp Lekhakula (The Scientific World Journal)
This study was aimed to assess the clinical significances of the serum VEGF and bFGF in Thai patients with de novo NHL. Serum VEGF and bFGF concentrations were measured from 79 adult patients with newly diagnosed stage 2–4 non-Hodgkin lymphomas by quantitative sandwich enzyme immunoassay. At the time of diagnosis, the serum VEGF concentrations from 79 patients ranged from 72.0 to 2919.4 pg/mL, with a mean of 668.0 pg/dL. The serum bFGF concentrations ranged from undetectable to 2919.4 pg/mL, with a mean of 12.15 pg/dL. Multivariate analysis identified higher than the mean of serum VEGF, B symptoms, bulky diseases, anemia, and treatment with CHOP or R-CHOP as independent variables influencing the complete remission rate. From a Cox proportional hazards model, variables independently associated with overall survival were bone marrow involvement, more extranodal involvement, poor performance status, anemia, and higher than the mean of serum bFGF.